KAJIAN SISTEMATIK LITERATUR: ANALISIS PENERAPAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Aristi, Jennya Zahra; Pujiastuti, Heni; Novaliyosi, Novaliyosi (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study was conducted because students’ mathematical problem-solving skills remain low, posing a challenge in the teaching and learning of mathematics in schools. The study aims to analyze the characteristics of the implementation of Problem-Based Learning (PBL) and its impact on students’ mathematical problem-solving skills. The method used was a Systematic Literature Review (SLR) comprising the stages of planning, implementation, and reporting. Data were obtained from scientific articles published between 2021 and 2026 via Google Scholar based on specific inclusion criteria and analyzed using the PRISMA approach, resulting in 15 relevant articles. The results of the study indicate that PBL has key characteristics, including the use of contextual problems, active student engagement, the systematic application of problem-solving stages, the development of higher-order thinking skills, and the teacher’s role as a facilitator. Additionally, PBL also enhances affective aspects such as student motivation and self-confidence. In terms of impact, PBL has been proven to have a positive and significant effect on students’ mathematical problem-solving skills, as evidenced by improved learning outcomes, differences in ability between the experimental and control groups, and increased learning mastery. Thus, PBL is effective in mathematics education for enhancing students’ problem-solving skills.